2021
DOI: 10.3390/ijms222111308
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Metabolic Analyses Reveal the Mechanism of Ethylene Production in Stony Hard Peach Fruit during Cold Storage

Abstract: Stony hard (SH) peach (Prunus persica L. Batsch) fruit does not release ethylene and has very firm and crisp flesh at ripening, both on- and off-tree. Long-term cold storage can induce ethylene production and a serious risk of chilling injury in SH peach fruit; however, the regulatory mechanism underlying ethylene production in stony hard peach is relatively unclear. In this study, we analyzed the phytohormone levels, fruit firmness, transcriptome, and lipidome changes in SH peach ‘Zhongtao 9’ (CP9) during col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 50 publications
(69 reference statements)
1
5
0
Order By: Relevance
“…In addition, genes related to ETH and ABA biosynthesis and signaling were also found to be up-regulated during the cold storage period. Similar ndings were also reported in stony hard peach (Wang et al 2021) and jujube fruit (Kou et al 2019). Since the over-accumulation of ETH and ABA is detrimental to postharvest crops (Cocetta and Natalini 2022), these results also suggested that active measures should be taken to the metabolic mechanism of ETH and ABA in cold stored okra pods.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, genes related to ETH and ABA biosynthesis and signaling were also found to be up-regulated during the cold storage period. Similar ndings were also reported in stony hard peach (Wang et al 2021) and jujube fruit (Kou et al 2019). Since the over-accumulation of ETH and ABA is detrimental to postharvest crops (Cocetta and Natalini 2022), these results also suggested that active measures should be taken to the metabolic mechanism of ETH and ABA in cold stored okra pods.…”
Section: Discussionsupporting
confidence: 84%
“…Among them, it is worth highlighting the indoleacetic acid (IAA) amido hydrolase enzymes, responsible for controlling the levels of IAA in plant cells by converting auxin-amino acid conjugates into free IAA molecules ( Bartel and Fink, 1995 ; LeClere et al, 2002 ). Although it was thought that this was their only function, it has recently been shown that these proteins can regulate the expression of the enzyme 1-aminocyclopropane-1-carboxylic (ACC) synthase (ACS), altering the synthesis of ethylene during peach ripening ( Wang et al, 2021 ). This would imply a new point of interaction between auxin metabolism and ET, whose possible implications in pepper fruit ripening could be interesting to address in future research.…”
Section: Discussionmentioning
confidence: 99%
“…At temperatures ranging between 0 and 15 °C, the plants experience cold or freezing stress. In general, freezing/cold stress can impact the growth and development by suppressing the true genetic potential of a plant which subsequently affects the metabolic processes and enzyme activity and its related fluidity of plant cell membranes, resulting in material and metabolic transport disorders as well as chilling injury [ 13 , 14 ]. Additionally, cold and freezing stress persuade cold-induced osmotic stress where plants experience cellular dehydration due to inhibition in water intake due to low temperatures [ 15 ].…”
Section: Abiotic Stress–freezing Stressmentioning
confidence: 99%